Teacher Training for the Design and Implementation of Virtual Learning Environments at the Elementary Sublevel - Tutiven Marquez, Liz Tamara; Untuña Soria, Victor Paul Untuña Soria; Jurado Martínez, Msc.María Gabriela; Alzate Peralta, Msc. Luis Alberto (Revista Minerva, 2025)
This study focuses on examining the design and implementation of Virtual Learning Environments (VLEs) in primary education in grades two, three, and four in Ecuador, with an emphasis on teacher training to improve their technological proficiency and foster creative and innovative teaching methods. The study identified deficiencies in teachers' access to technical resources and digital skills and proposes addressing these weaknesses through targeted training sessions. To achieve this, a quantitative strategy was employed that included assessments, seminars, and surveys with 12 teachers at the Milenium Educational Unit in Guayaquil. The results of the VLE implementation at the school show notable improvements in teachers' digital skills in the use of technological resources. However, they face challenges such as workload management, limitations of digital infrastructure, and unequal access to technology, with 38.5% not receiving training in the use of technological tools. The study concludes that to modernize educational methods and ensure equitable and dynamic learning experiences, it is essential to include virtual learning environments (VLEs) in the curriculum through ongoing teacher training and investment in technology.